A porous medium-chain-length poly(3-hydroxyalkanoates)/hydroxyapatite composite as scaffold for bone tissue engineering - Ansari, Nor Faezah; Annuar, Mohamad Suffian; Murphy, Belinda-pingguan (Wiley-VCH Verlag, 2017)
Polyhydroxyalkanoates (PHA) are hydrophobic biopolymers with huge potential for biomedical applications due to their biocompatibility, excellent mechanical properties and biodegradability. A porous composite scaffold made of mediumchain- length poly(3-hydroxyalkanoates) (mcl-PHA) and hydroxyapatite (HA) was fabricated using particulate leaching technique and NaCl as a porogen. Different percentages of HA loading was investigated that would support the growth of osteoblast cells. Ultrasonic irradiation was applied to facilitate the dispersion of HA particles into the mcl-PHA matrix. The different P(3HO-co-3HHX)/HA composites were investigated using field emission scanning electron microscopy (FESEM), X-ray diffraction (XRD) and energy dispersive X-ray analysis (EDXA). The scaffolds were found to be highly porous with interconnecting pore structures and the HA particles were homogeneously dispersed in the polymer matrix. The scaffolds biocompatibility and osteoconductivity were also assessed following the proliferation and differentiation of osteoblast cells on the scaffolds. From the results, it is clear that scaffolds made from P(3HO-co-3HHX)/HA composites are viable candidate materials for bone tissue engineering applications.